Extended pancreato-duodenectomy coupled with adjuvant chemotherapy for SMARCB1/INI1 deficient pancreatic carcinoma: A case report and literature review. (May 2021) - Mugaanyi, Joseph; Lu, Changjiang; Lu, Caide; Wang, Chunnian
Abstract: Introduction: SMARCB1/INI1 gene deletion appears to be associated with a rare, malignant and aggressive form of pancreatic carcinoma whose diagnosis is challenging. Our objective is to illustrate that the tumor may masquerade as a duodenal papillary carcinoma, be difficulty to identify on diagnostic imaging and that making an accurate diagnosis may be challenging, however surgical resection may be possible. Case report: We present a case of a 24-year old male patient presenting with jaundice and itchy skin, elevated TBIL, AST, ALP and CA125. A 2.2 × 1.7 cm pancreatic nodule, later diagnosed as a SMARCB1/INI deficient pancreatic carcinoma was detected on Endoscopic Ultrasound - Fine Needle Aspiration (EUS-FNA). The patient was successfully treated with extended pancreato-duodenectomy coupled with adjuvant chemotherapy, a 7 × 5 × 5 cm tumor resected. Discussion: SMARCB1/INI deficient pancreatic carcinoma has been reported in couple of other articles. However, unlike other cases, in our case identification and accurate assessment of the tumor was particularly difficulty both on imaging and during operation. Our patient has thus far had a positive outcome with no recurrence. Conclusion: For rare forms of pancreatic carcinoma, identification and assessment of the tumor size may be challenging on imaging and during operation. However, careful assessment should be performed before ruling out surgical resection. Furthermore, adjuvant chemotherapy may be beneficial to the patient. Highlights: SMARCB1/INI gene deletion is associated with undifferentiated carcinoma characterized by malignancy and aggressiveness. This case highlights the ambiguity in manifestation and diagnosis of SMARCB1 pancreatic carcinoma. Assessment and accurate determination of the tumor size may not be possible on imaging and preoperatively. Adjuvant chemotherapy may be beneficial to patient prognosis post-surgery.